Vascular Endothelial Growth Factor Signaling in Models of Oxygen-Induced Retinopathy: Insights Into Mechanisms of Pathology in Retinopathy of Prematurity - Ramshekar, Aniket; Hartnett, M. Elizabeth (Frontiers in pediatrics, 2021)
Retinopathy of prematurity (ROP) is a leading cause of blindness in children worldwide. Blindness can occur from retinal detachment caused by pathologic retinal angiogenesis into the vitreous, termed intravitreal neovascularization (IVNV). Although agents that interfere with the bioactivity of vascular endothelial growth factor (VEGF) are now used to treat IVNV, concerns exist regarding the identification of optimal doses of anti-VEGF for individual infants and the effect of broad VEGF inhibition on physiologic angiogenesis in external organs or in the retina of a preterm infant. Therefore, it is important to understand VEGF signaling in both physiologic and pathologic angiogenesis in the retina. In this manuscript, we review the role of receptors that interact with VEGF in oxygen-induced retinopathy (OIR) models that represent features of ROP pathology. Specifically, we discuss our work regarding the regulation of VEGFR2 signaling in retinal endothelial cells to not only reduce severe ROP but also facilitate physiologic retinal vascular and neuronal development.